Chromosome misalignments induce spindle‐positioning defects. (4th February 2016) - Tame, Mihoko A; Raaijmakers, Jonne A; Afanasyev, Pavel; Medema, René H
Abstract: Cortical pulling forces on astral microtubules are essential to position the spindle. These forces are generated by cortical dynein, a minus‐end directed motor. Previously, another dynein regulator termed Spindly was proposed to regulate dynein‐dependent spindle positioning. However, the mechanism of how Spindly regulates spindle positioning has remained elusive. Here, we find that the misalignment of chromosomes caused by Spindly depletion is directly provoking spindle misorientation. Chromosome misalignments induced by CLIP‐170 or CENP‐E depletion or by noscapine treatment are similarly accompanied by severe spindle‐positioning defects. We find that cortical LGN is actively displaced from the cortex when misaligned chromosomes are in close proximity. Preventing the KT recruitment of Plk1 by the depletion of PBIP1 rescues cortical LGN enrichment near misaligned chromosomes and re‐establishes proper spindle orientation. Hence, KT‐enriched Plk1 is responsible for the negative regulation of cortical LGN localization. In summary, we uncovered a compelling molecular link between chromosome alignment and spindle orientation defects, both of which are implicated in tumorigenesis. Synopsis: Chromosome misalignments result in the cortical displacement of LGN, followed by defects in spindle positioning. The disruption of cortical LGN is caused by kinetochore‐associated PLK1 on the uncongressed chromosomes. Chromosome alignment defects entail perturbations in spindle positioning. Misaligned chromosomes actively disrupt the cortical association of LGN. Kinetochore‐associated PLK1 on misaligned chromosomes negatively regulates LGN localization at the cortex. Abstract : Chromosome misalignments result in the cortical displacement of LGN, followed by defects in spindle positioning. The disruption of cortical LGN is caused by kinetochore‐associated PLK1 on the uncongressed chromosomes.